Percentiles and Reference Values for Accelerometric Gait Assessment in Women Aged 50–80 Years - Raquel Leirós-Rodríguez; Jesús García-Liñeira; Anxela Soto-Rodríguez; Jose L. García-Soidán (Brain Sciences, 2020)
Background: The identification of factors that alter postural stability is fundamental in the design of interventions to maintain independence and mobility. This is especially important for women because of their longer life expectancy and higher incidence of falls than in men. We constructed the percentile box charts and determined the values of reference for the accelerometric assessment of the gait in women. Methods: We used a cross-sectional study with 1096 healthy adult women, who were asked to walk a distance of 20 m three times. Results: In all of the variables, a reduction in the magnitude of accelerations was detected as the age of the group advanced. The box charts show the amplitude of the interquartile ranges, which increases as the age of the participants advances. In addition, the interquartile ranges were greater in the variables that refer to the maximum values of the accelerations. Conclusions: The values obtained can be used to assess changes in gait due to aging, trauma and orthopaedic alterations that may alter postural stability and neurodegenerative processes that increase the risk of falling.